Gyselaaronderhandeling as oorreding - Petra Theunissen; Andrea Crystal; Sonja Verwey (Communicare)
The use of negotiation in hostage situations is not a new concept. As a matter of fact, it has been used worldwide since the 1970's. However, the South African Police Service (SAPS) has been training its members in the use of hostage negotiations only since 1990. Seen in the light of greater community involvement by the SAPS it is expected that hostage negotiation as a nonviolent means of solving such situations will become more common as time goes by. In this article hostage negotiation is viewed as a form of persuasive communication. It focuses on the existence of and reasons for resistance to the persuasive content of hostage negotiations. Strategies that the hostage negotiator can use to overcome existing resistance are discussed, as well as strategies and techniques to initiate change in the hostage taker's behaviour, that is, to persuade the latter to let the hostage go unharmed the ultimate goal of such negotiations. Recommendation is made that South African hostage